The Role of Strategic Capital in Achieving Competitive Advantage - عثمان حسن محسن; على حسن سفين (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
This research sought to know the role of strategic capital in achieving competitive advantage in universities under study the research, in addition to analyzing the correlation and influence relationship between its dimensions represented in (strategic commitment, Suport the implemention of the strategy, Effectiveness of strategic implementation, Organizational learning) in the dimensions of competitive advantage in:(cost, quality, flexibility, speed and delivery, creativity and innovation). The research problem was highlighted by raising several questions about the nature of the correlation and influence between the independent variable (strategic capital) and the dependent variable (competitive advantage). For this, a hypothesis scheme was designed from which two hypotheses emerged, and in order to ensure their validity, they were subjected to multiple tests. The research used a questionnaire as a tool in the data collection process. The research has adopted the descriptive analytical approach, as the main and sub-variables were described, to analyze the relationships and influence between the variables. The research population were the 9 private universities in the city of Erbil. The researcher has selected five of them as research sample, while the respondents were (105) members of the college councils in the study sample. The hypotheses were tested through a set of analyzes and statistical tests using the computer program (SPSS Ver. 26). The research shows a high positive and with statistical significance relationship between strategic capital and competitive advantage at the macro and micro levels. This paper suggests a set of ideas, among which is how vital it is to invest in a strong relationship between strategic capital and competitive advantage and directing this relationship towards assisting private universities.